2016
DOI: 10.1073/pnas.1603984113
|View full text |Cite
|
Sign up to set email alerts
|

Musical intervention enhances infants’ neural processing of temporal structure in music and speech

Abstract: Individuals with music training in early childhood show enhanced processing of musical sounds, an effect that generalizes to speech processing. However, the conclusions drawn from previous studies are limited due to the possible confounds of predisposition and other factors affecting musicians and nonmusicians. We used a randomized design to test the effects of a laboratory-controlled music intervention on young infants' neural processing of music and speech. Nine-month-old infants were randomly assigned to mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 54 publications
5
107
0
2
Order By: Relevance
“…To model this vestibular input, future iterations of the model could include a motor network that is stimulated with periodic input (e.g., a sinewave) at the frequency of caregivers’ bouncing. Fourth, future iterations of the model could investigate perceptual reorganization to musical rhythm that occurs on shorter timescales, such as modeling the effects of active, short‐term musical training on infants’ perception and neural processing of rhythms . Finally, as rhythmic variability is likely a rich source of input that contributes to listeners' knowledge of metrical structure over development, we intend to increase the training material to include a corpus of isochronous‐ and nonisochronous‐metered rhythms in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To model this vestibular input, future iterations of the model could include a motor network that is stimulated with periodic input (e.g., a sinewave) at the frequency of caregivers’ bouncing. Fourth, future iterations of the model could investigate perceptual reorganization to musical rhythm that occurs on shorter timescales, such as modeling the effects of active, short‐term musical training on infants’ perception and neural processing of rhythms . Finally, as rhythmic variability is likely a rich source of input that contributes to listeners' knowledge of metrical structure over development, we intend to increase the training material to include a corpus of isochronous‐ and nonisochronous‐metered rhythms in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these early behavioral responses speak for an ability to detect rhythm and tempo and violation of these temporal patterns have been detected by electroencephalogram studies in two month-old infants (Otte et al, 2013) and in newborns (H aden et al, 2015). Recently, using magnetoencephalography in 9-month-old infants, Zhao and Kuhl (2016) showed that a music intervention in a social environment for one month (12 sessions of 15 min) increased mismatch responses in auditory and prefrontal cortical regions to temporal violation in music and speech. Thus, the authors suggested that repeated music intervention might modify not only music processing abilities, but also speech processing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the influences of cognitive skills on speech perception in this period; 11-month old monolingual infants show a strong negative correlation Zhao and Kuhl (2016) between specific cognitive controls skills (inhibitory control) and nonnative speech discrimination (Conboy, Sommerville, and Kuhl 2008;Diamond, Werker, and Lalonde 1994;Lalonde and Werker 1995). The authors' interpretation is that infants with good inhibitory control skills are better able to ignore speech sounds that are irrelevant to their native language, and, therefore, that they exhibit lower nonnative speech discrimination skills, which has been shown to correlate with faster native-language growth (Figure 2; Kuhl et al 2008).…”
Section: Summary and Discussionmentioning
confidence: 81%
“…Decades of research have demonstrated that infants' ability to discriminate native speech contrasts Source: Adapted from Zhao and Kuhl (2016) improves, in contrast to their ability to discriminate nonnative speech contrasts that decreases during this period Werker and Tees 1984). Further, we discussed that infants' phonetic learning during this sensitive period is highly malleable, depending on the auditory input infants receive at that time.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 1 more Smart Citation